Etika Penggunaan Teknologi Smartphone Dikalangan Remaja Dalam Meningkatkan Kesadaran Kewarganegaraan - Wahyuni, Andi Sri Sri; Nursalim, Nursalim; Marsuki, Andika (Universitas Syiah Kuala, 2025)
The rapid advancement of technology has a great impact on the world community. One such technology is smartphones. Nowadays, smartphone technology is an inseparable part of daily life, especially among teenagers. In addition to the benefits obtained when smartphones are used wisely, their unwise use will also pose various challenges. In the context of citizenship, this phenomenon can impact a lack of understanding of democratic values, rights, and obligations as citizens, as well as active participation in building a civilized and responsible society. The purpose of this study is to find out how the ethics of using smartphone technology among adolescents increase civic awareness. This study uses a descriptive qualitative method that utilizes the type of literature research. The data obtained will be analyzed to find the main problems and find solutions to the problems. The results of this study show that with an understanding of digital ethics, wise in managing information, using social media productively, balancing digital life and the real world, and participating in digital awareness campaigns, it is very necessary to continue to build civic awareness as the younger generation, especially among teenagers to remain wise in the use of smartphone technology.